A collection assessment of Bachelor of Sports Science in College of Human Kinetics Library in the University of the Philippines Diliman - Eugenio, Lucan L. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
Every library should conduct a periodic collection assessment to ensure that their collection is up-to-date and relevant to the needs of their users. Collection assessment provides an organized analysis that helps librarians to improve its library collection in line with the users' needs.